Research of the Transfer Method of Four-dimensional Coordinate to Three-dimensional Coordinate - Ran Xiaoyan; Zhang Bai (Jixie chuandong)
The coordinate measure machine（CMM） with rotary table is often use in the field of precision measurement.Because of the error evaluation requires that all measured point must be expressed in the same coordinate system,but the workpiece coordinate system is changed in the process of measuring because of rotation of rotary table,so it is difficult to evaluate errors.Therefore,a model for coordinate transfer from four-dimensional coordinate system to three- dimensional coordinate system is created.Through the transfer algorithm of coordinate system,the four- dimensional coordinate with rotary table can be transferred to a three dimension Cartesian coordinate by utilizing rotary table coordinate system to act as medial coordinate system,then,it can be transferred to workpiece coordinate system or machine coordinate system,sequentially,the error evaluation is realized.The experimental results show that the mathematical model is right,and it can meet the requirement of precise measurement.